The State of Manufacturing Industry in the Republic of Serbia and Its Potentials for Cooperation with the People's Republic of China. (1st January 2020) - Lalic, Bojan; Zivlak, Nikola; Todorovic, Tanja; Marjanovic, Ugljesa
In recent years, Industry 4.0 or Internet +, has been introduced as a popular term to describe the trend in industrial production towards digitization and automation of the manufacturing environment. This paper presents the overview of European Manufacturing Survey conducted in manufacturing industries in transitional economy – the Republic of Serbia. The current Serbian dataset of 2015 includes 280 observations of Serbian firms of all manufacturing industries. Empirical results indicate that manufacturing companies in Serbia have a lot of room for improvements in the following areas: automation and robotics, energy and resource efficiency, processing techniques for new materials, additive manufacturing technologies, and digital factory. This can be done through cooperation with the People's Republic of China.